Situating Food Industry Influence: Governance Norms and Economic Order; Comment on "'Part of the Solution': Food Corporation Strategies for Regulatory Capture and Legitimacy" - Raphael Lencucha (Kerman University of Medical Sciences, 2022)
Lacy-Nichols and Williams provide important new insights into the ongoing contest over policy space and consumer behavior. I attempt to situate these insights in relation to government mandates and governance norms and situate these norms and mandates in the prevailing economic order. This approach is necessary to understand how corporate practices persist and why governments are receptive to the approaches outlined in the analysis conducted by Lacy-Nichols and Williams. This approach can help explain why governments are often receptive to corporations positioning themselves as 'part of the solution'. Governments want strong economies and big food positions itself as contributor to this end. The point I attempt to articulate is that we often conceive of corporate power as power over, while I suggest that corporate power is rather power within and through a system that is oriented towards profits and economic growth.